Professional support and emergency visits during the first 2 weeks postpartum. Issue 1 (15th March 2013) - Barimani, Mia; Oxelmark, Lena; Johansson, Sven‐Erik; Langius‐Eklöf, Ann; Hylander, Ingrid
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to assess mothers' perceived satisfaction with professional support during the first 2 weeks after childbirth and the extent to which mothers seek emergency care during the same period. Design A cross‐sectional study was conducted of all mothers (n = 546) in Stockholm County, Sweden, who gave birth to a live baby during the same week in 2009. Ethical issues The study was approved by the regional Research and Ethics Committee at the Karolinska Insititutet, Sweden. Methods The mothers responded to a study‐specific questionnaire on perceived satisfaction with professional support and the sense of coherence scale, which measures coping strategies. The mothers also provided information about their socio‐demographic background, obstetric and infant data, and visits to hospital emergency departments. Descriptive and logistic regression analyses were performed. Results Fifty‐three percent of the mothers rated the support received as sufficient or more than sufficient, 29.7% as neither sufficient nor insufficient and 17.7% as insufficient or completely insufficient. The results indicate a lack of continuity in postpartum care. As many as 17% of the mothers in the study population visited hospital emergency departments during the first 2 weeks after childbirth, as a result of problems related to delivery, breastfeeding or infant health. A higher frequency of such emergency visits was associated with poor perception of professional support, low sense of coherence and delivery complications. Conclusions Relative to otherwise comparable mothers, mothers who experience complications with delivery are less satisfied with professional support and turn more frequently to hospital emergency departments for support.